Uji Kualitas Material Bahan Konstruksi Beton Pada Gedung Pastori Tiga Gmim Yudea Paal Dua - Tulaka, Titof (Jurnal Ilmiah Wahana Pendidikan, 2025)
The development of science in the field of construction in Indonesia at present is very rapid, including in the construction of housing, offices, high-rise buildings, hospitals, bridges and other infrastructure. To achieve high concrete quality, it is very dependent on the materials of sand, gravel and reinforced concrete used in the planned construction. Therefore, from the principles stated above, a number of problems related to concrete quality can be identified, considering the scope of the problem is very broad, so not all of the above problems are studied the actual concrete design content. The purpose of this study is to determine the Quality of Concrete Construction Materials in the Pastori Tiga Building of GMIM Yudea Paal Dua and is expected to provide general information in the world of Civil Engineering and for areas that have natural resources so as not to cause doubts in its use as a coarse aggregate in a concrete mixture whether it can be in accordance with the desired or expected quality. The method used in this study is the Exploratory Survey Method where this method is used to determine the quality of sand and gravel building materials, through laboratory testing. To obtain data on the quality characteristics of sand and gravel quality, these materials are tested through the laboratory by assuming the regulatory instructions regarding the quality testing of sand and gravel quality according to PBI 1971 NI. The data analysis results obtained showed that the sand tested, from Manado City, was suitable for use because it met the requirements of ASTM C 35-37, PBI-71, NI 2, and did not require washing. The gravel tested, from Manado City, was unsuitable for use because it did not meet the requirements of ASTM or PBI-71 and required gradation improvement. This was due to the presence of grains larger than 31.5 mm.